Implementação da Política Nacional de Atenção Integral à Saúde do Homem (PNAISH) no município de Ponta Grossa – Paraná - Alves, Franciele Koehler (2016)
To reflect on men’s health is to think about public health, and on the way that people experience the health-disease-care process and organize both coping and disease prevention and other vulnerabilities that affect life quality. The way men and women care their health differs, wich includes the way they socialize, according to the gender they belong to. Studies based on Brazilian reality revealed that men often seek health services when they are already suffering from some disease or accident. Aiming to stimulate the expansion and qualification of attention to male health under the National Health System, especially in primary attention, the Ministry of Health established by Decree n. 1944/2009, the National Policy to Integral Attention to Men's Health (Política Nacional de Atenção Integral à Saúde do Homem - PNAISH). And after seven years his proposition, as is the implementation of this policy in Ponta Grossa? They are being developed actions to strengthen the PNAISH scope of primary care? In addition, the perception of nurses and managers involved on the comprehensive health care of man in the city? Which are the perspectives and challenges to health care and this public implementation of the policy? Thus, the present study mainly objective was to analyze the implementation of PNAISH in Ponta Grossa - Paraná. Considering the complexity of the object, which runs through interdisciplinarity, we conducted a study case with quantitative and qualititative approach through triangulation: literature review, document study, observation, interviews with health professionals (questionnaires) and managers. The data was processed and analyzed continuously under the light of analysis content, emerging as categories of analysis the five axes of PNAISH: access and host; sexual and reproductive health; paternity and care; diseases prevalent in the male population; prevention of violence and accidents. As results also presented some challenges and perspectives on such implementation, especially with regard to gender and masculinities. It stayed evident from completion of this investigation that although they were developed some actions that affect the specificity of the male population between 20 and 59 years, yet the health policy of the man does not seem to make up the health agenda in Ponta Grossa. Thus, yet still need to invest in the capacitation of the work teams and dissemination of PNAISH mobilization of mend besides, favoring both access to and reception of these services, especially in the context of primary care - given the fact that the municipality there are still socio-cultural, institutional and relational barriers cited in the literature on the subject. It was the exploitation.